How do people cope with stress? An assessment using partial least squares - Arbaiza, Lydia (2018)
Work stress resulting from lack of coping strategies is a problem that affects several organizations. This study aimed to identify the level of perceived stress, and coping styles in a sample of 120 executives in Peru. Coping strategies for stress were also classified using three categories: problem centered, emotion centered, and other coping. The results showed that the executives experienced a moderate level of stress, and preferred a coping style centered on meaning or perception (i.e., emotion and other coping). This is based on: the individuals’ values and beliefs and strategies, such as positive reinterpretation, acceptance, denial, turning to religion, Emotional social support, focus on & venting emotions, and behavioral disengagement goal review, concentration on strengths gained from life experience, and reorganization of priorities. These results are relevant to human resources policies that support strategies for reducing stress and increasing employees’ productivity in the workplace. We also analyzed and tested whether cope comes from a collectivism influence.